A chromogenic and ratiometric fluorogenic probe for rapid detection of a nerve agent simulant DCP based on a hybrid hydroxynaphthalene–hemicyanine dye. Issue 28 (4th July 2017) - Ali, Syed Samim; Gangopadhyay, Ankita; Maiti, Kalipada; Mondal, Sanchita; Pramanik, Ajoy Kumar; Guria, Uday Narayan; Uddin, Md. Raihan; Mandal, Sukhendu; Mandal, Debasish; Mahapatra, Ajit Kumar
Abstract : A new cyanine dye (CYD ) has been synthesized for DCP sensing. Abstract : A new cyanine dye (CYD ) based on hybrid hydroxynaphthalene–hemicyanine has been synthesized and characterized. The chromogenic and ratiometric fluorogenic probe (CYD ) enables a fast and highly sensitive response to an OP nerve agent mimic diethyl chlorophosphate (DCP ) through tandem phosphorylation and intramolecular cyclization reaction within 1 min and with the detection limit as low as 18.86 nM. To our knowledge this is the first report of a hydroxyl assisted bathochromic shift in a selective chemodosimeter forDCP exhibiting a ratiometric response. TDDFT calculations were performed in order to demonstrate the electronic properties of the probe and the cyclized product. Moreover, the utility of the probeCYD for the detection ofDCP in live cells, in the gas phase and in a spiked soil sample has also been demonstrated.